Investigating the Effect and Immunity of Tissue Plasminogen Activator in the Treatment of Acute Ischemic Stroke - Shamsaei, Gholam Reza; Rafie, Shahram; Rahimi, Zeinab (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Background and Objective: Although current evidence has demonstrated the efficacy and immunity of Alteplase, further studies are needed to evaluate its functioning in the therapeutic system. This study aims to assess the effect and immunity of tissue plasminogen activator (tPA) in the treatment of acute ischemic stroke (AIS). Methods: This study was conducted as a retrospective observational study on patients with AIS referred to Ahvaz Golestan Hospital in 2017-2018. By using the hospital database, demographic information, the cause of lack of thrombolytic therapy, the onset of symptoms and admission were extracted. The National Institutes of Health Stroke Scale (NIHSS) at the time of referral, 24 hours after treatment, and at the time of discharge, the modified Rankin Scale (mRS) scores at discharge time and 3 months after discharge, complications and mortality at the time of admission and 3 months after discharge were recorded. Results: The mean of the event to needle (hrs) was significantly lower in the tPA group (P <0.0001), and delay in visiting time and loss of golden time were of the main reasons for not receiving tPA in the control group. The mean difference and the decrease in NIHSS score 24 hours after admission and discharge in the tPA group was significantly higher (P <0.0001). At the time of discharge, the mean score of mRS in the two groups was not significantly different. Three months after treatment, the mean score of mRS in the tPA group was significantly lower than that in the control group (P <0.05). The percentage of patients with bleeding complications was higher in the tPA group (7.27%) than that in the control group (4.89%). The percentage of deaths during the hospital stay in the tPA group (3.64%) was higher than that in the control group (1.63%). Conclusion: Patients with AIS under intravenous thrombolytic therapy with tPA showed improvement in functional measurements and neurological outcomes compared with the control group. Lack of significant difference in the rate of complications and mortality between the two groups indicated the safety and high efficacy of thrombolytic therapy in patients with AIS